Si/Al derived opal concentrations of IODP Site U1537 - Hallmaier, Moritz; Gutjahr, Marcus; Lippold, Jörg; Hemming, Sidney R; Gerber, Lukas; Weber, Michael E; Eisenhauer, Anton (In: Hallmaier, M et al. (2025): Authigenic Uranium Preservation and Bottom Water Oxygenation in the Scotia Sea [dataset bundled publication]. PANGAEA, https://doi.org/10.1594/PANGAEA.982959, 2025)
We calculated the opal content by normalizing XRF based Si/Al-ratios with FTIRS based biogenic opal measurements. This shows a much stronger correlation (R=0.96) for the last 300 kyr than b* and opal content (R=0.77) (Weber et al. 2022).
Keywords: authigenic uranium; Biogenic Barium (xsBa); bottom-water oxygenation; export productivity; opal; Scotia Sea; sediment; Southern Ocean; Th; thorium normalization; Weddell Sea